The Potential Use of Allogeneic Platelet-Rich Plasma for Large Bone Defect Treatment: Immunogenicity and Defect Healing Efficacy. Issue 1 (January 2013) - Zhang, Zhi-Yong; Huang, Ai-Wen; Fan, Jun Jun; Wei, Kuanhai; Jin, Dan; Chen, Bin; Li, Dan; Bi, Long; Wang, Jun; Pei, Guoxian
Autologous platelet-rich plasma (PRP) has been extensively investigated for large bone defect treatment, but its clinical application is harassed by controversial outcome, due to highly variable PRP quality among patients. Alternatively, allogeneic PRP from well-characterized donors cannot only generate more consistent and reliable therapeutic effect but also avoid harvesting large quantities of blood, an additional health burdens to patients. However, the use of allogeneic PRP for bone defect treatment is generally less investigated, especially for its immunogenicity in such application. Here, we meticulously investigated the immunogenicity of allogeneic PRP and evaluated its healing efficacy for critical-sized defect treatment. Allogeneic PRP contained 4.1-fold and 2.7- to 4.9-fold higher amount of platelets and growth factors than whole blood, respectively. The intramuscular injection of allogeneic PRP to rabbits did not trigger severe and chronic immunoresponse, evidenced by little change in muscular tissue microstructure and CD4 + /CD8 + T lymphocyte subpopulation in peripheral blood. The implantation of allogeneic PRP/deproteinized bone matrix (DPB) constructs (PRP + DPB) successfully bridged 1.5-cm segmental radial defects in rabbits, achieving similar healing capacity as autologous MSC/DPB constructs (MSC + DPB), with greater bone formation (1.1–1.5x, p < 0.05) and vascularization (1.3–1.6x, p < 0.05) than DPB alone, shown by histomorphometric analysis, bone mineral density measurement, and radionuclide bone imaging. Furthermore, the implantation of both allogeneic PRP- and autologous MSC-mediated DPB constructs (PRP + MSC + DPB) resulted in the most robust bone regeneration (1.2–2.1x, p < 0.05) and vascularization (1.3–2.0x, p < 0.05) than others (PRP + DPB, MSC + DPB, or DPB alone). This study has demonstrated the promising use of allogeneic PRP for bone defect treatment with negligible immunogenicity, great healing efficacy, potentially more consistent quality, and no additional health burden to patients; additionally, the synergetic enhancing effect found between allogeneic PRP and autologous MSCs may shed a light on developing new therapeutic strategies for large bone defect treatment.